Pura Siwa Jagat Karana sebagai Pusat Orientasi Keagamaan, Sosial, dan Budaya Masyarakat Hindu Bali di Kota Ternate - Arvita Ratib; Putu Karina Pravitasari; Gede Budarsa (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research examines the role of Pura Siwa Jagat Karana as the orientation center of the Balinese Hindu community in Ternate City, functioning not only as a place of worship but also as a hub for social and cultural activities. The study aims to describe the role of Pura Siwa Jagat Karana in the religious, social, and cultural life of the Balinese Hindu community and to analyze the challenges faced in sustaining its existence within a multicultural society. The research employs Emile Durkheim’s Structural Functionalism theory, emphasizing the role of religious institutions in maintaining social integration. A qualitative approach was applied, using observation, in-depth interviews, and documentation. The findings reveal that Pura Siwa Jagat Karana functions as a spiritual center, a medium for preserving Balinese culture, and a means of strengthening solidarity and identity of the Balinese Hindu community. Nevertheless, the temple faces several challenges, including limited accessibility for worshippers, changes in management, insufficient ritual facilities, dynamics in priest leadership, and constrained resources. Despite these obstacles, the temple continues to serve as a symbol of harmony and a space for interfaith dialogue that fosters peace in the heterogeneous society of Ternate.